In vivo investigation of the tissue response to commercial Teflon insulin infusion sets in large swine for 14 days: the effect of angle of insertion on tissue histology and insulin spread within the subcutaneous tissue - Eisler, Gabriella (BMJ Open Diabetes Res Care, 2019)
OBJECTIVE: This study investigated the effects of the inflammatory tissue response (ITR) to an insulin infusion set (IIS) on insulin bolus spread over wear time, as well as the effect of cannula insertion angle on the ITR, bolus shape, and pump tubing pressure. RESEARCH DESIGN AND METHODS: Angled or straight IISs were inserted every other day for 14 days into the subcutaneous tissue of 11 swine and insulin was delivered continuously. Prior to euthanasia, a 70 µL bolus of insulin/X-ray contrast agent was infused while recording a pressure profile (peak tubing pressure, p(max); area under the pressure curve, AUC), followed by the excision of the tissue-catheter specimen. Bolus surface area (SA) and volume (V) were assessed via micro-CT. Tissue was stained to analyze total area of inflammation (TAI) and inflammatory layer thickness (ILT) surrounding the cannula. RESULTS: A bolus delivered through an angled IIS had a larger mean SA than a bolus delivered through a straight cannula (314.0±84.2 mm(2) vs 229.0±99.7 mm(2), p<0.001) and a larger volume (198.7±66.9 mm(3) vs 145.0±65.9 mm(3), p=0.001). Both decreased significantly over wear time, independent of angle. There was a significant difference in TAI (angled, 9.1±4.0 mm(2) vs straight, 14.3±8.6 mm(2), p<0.001) and ILT (angled, 0.7±0.4 vs straight, 1.2±0.7 mm, p<0.001). p(max) (p=0.005) and AUC (p=0.014) were lower using angled IIS. As ILT increased, p(max) increased, while SA and V decreased. CONCLUSIONS: The progression of the ITR directly affected bolus shape and tubing pressure. Although straight insertion is clinically preferred, our data suggest that an angled IIS elicits lower grades of ITR and delivers a bolus with lower tubing pressure and greater SA and V. The subcutaneous environment plays a crucial role in IIS longevity, and the insertion angle needs to be considered in future IIS designs and clinical trials.